Series estadisticas de precios promedios corrientes de frijol a nivel de consumidor en Cali y Palmira Valle del Cauca. Periodo 1977- 1989 - Calderón, W (International Center for Tropical Agriculture, 1990)
Statistics are presented of bean prices and av. prices (Col$/lb) for the consumer in the markets of Cali and Palmira (Valle del Cauca, Colombia), for the period from Feb. 1977 to Dec. 1989. This data base is the foundation for further marketing studies with common beans. (AS-CIAT)